2008
DOI: 10.1128/mcb.00074-08
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Type Protein Tyrosine Phosphatase ζ-Pleiotrophin Signaling Controls Endocytic Trafficking of DNER That Regulates Neuritogenesis

Abstract: Protein tyrosine phosphatase (PTP) is a receptor type protein tyrosine phosphatase that uses pleiotrophin as a ligand. Pleiotrophin inactivates the phosphatase activity of PTP, resulting in the increase of tyrosine phosphorylation levels of its substrates. We studied the functional interaction between PTP and DNER, a Notch-related transmembrane protein highly expressed in cerebellar Purkinje cells. PTP and DNER displayed patchy colocalization in the dendrites of Purkinje cells, and immunoprecipitation experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…Nevertheless, the robust expression of this molecule suggests that there may be other roles for DNER that eluded our analysis. Interestingly, DNER was recently shown to be actively endocytosed by a protein tyrosine phosphatase and inhibit neurite outgrowth in Neuro-2A cells (Fukazawa et al 2008) …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the robust expression of this molecule suggests that there may be other roles for DNER that eluded our analysis. Interestingly, DNER was recently shown to be actively endocytosed by a protein tyrosine phosphatase and inhibit neurite outgrowth in Neuro-2A cells (Fukazawa et al 2008) …”
Section: Discussionmentioning
confidence: 99%
“…2F). (57) and neuritogenesis (58) in mouse and in the in vitro and in vivo growth of human glioblastomas (40,59,60). As previous studies have shown that PTN inhibits the growth of glioblastomas, to determine the functional relevance of PTP-receptor engagement by IL-34, we tested the effects of IL-34 and PTN on the U251 glioblastoma cells expressing either PTP-or scrambled (control) shRNA.…”
Section: Hil-34 Binds To Cell Surface Ptp-on U251 Glioblastomamentioning
confidence: 99%
“…78) Delta/Notch-like epidermal growth factor (EGF)-related receptor (DNER) is a transmembrane protein highly expressed in cerebellar Purkinje cells along with co-localization of RPTPζ. 79) Normal DNER is endocytosed and inhibits the retinoic-acid-induced neurite outgrowth of Neuro-2A cells. PTN stimulation inhibits the RPTPζ phosphatase activity and increases the tyrosine phosphorylation level of DNER and suppresses the endocytosis of this protein.…”
Section: )mentioning
confidence: 99%
“…PTN stimulation inhibits the RPTPζ phosphatase activity and increases the tyrosine phosphorylation level of DNER and suppresses the endocytosis of this protein. 79) Phosphorylated DNER accumulates on the plasma membrane and induces neurite outgrowth, probably though Notch signal pathway which has important roles in cell-cell adhesion and cell differentiation. 79) Fyn is a tyrosine kinase belonging to the Src family and involves in the cell plasticity, cell-cell adhesion, cell migration and cell proliferation.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation